2015
DOI: 10.1111/1752-1688.12347
|View full text |Cite
|
Sign up to set email alerts
|

Using Fly Ash as a Marker to Quantify Culturally‐Accelerated Sediment Accumulation in Playa Wetlands

Abstract: Wetlands in the Rainwater Basin in Nebraska are vulnerable to sediment accumulation from the surrounding watershed. Sediment accumulation has a negative impact on wetland quality by decreasing the depth and volume of water stored, and the plant community species composition and density growing in the wetland. The objective of this study was to determine the amount of sediment that has accumulated in five selected wetlands in the Rainwater Basin in Nebraska. Soil cores were taken at five or six locations along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The 95 % CIs for our comparative sample overlapped with the 95 % CIs reported by Gleason (2001) for seasonal and semipermanent across the Prairie Pothole Region (Montana, North Dakota, South Dakota, Minnesota, and Iowa) embedded in both grasslands and croplands; our point estimates were nonsignificantly lower. An empirical study conducted in the neighboring state of Nebraska reported similar annual sediment accumulation rates ranging from 0.18 cm yr −1 to 0.29 cm yr −1 (Tang et al 2015). Wetlands embedded in agricultural fields had greater (non-overlapping 95 % CIs) annual sediment accumulation rates than wetlands surrounded by predominantly grassland in both Gleason's and our studies ( Table 2).…”
Section: Comparison With Empirical Studiessupporting
confidence: 71%
“…The 95 % CIs for our comparative sample overlapped with the 95 % CIs reported by Gleason (2001) for seasonal and semipermanent across the Prairie Pothole Region (Montana, North Dakota, South Dakota, Minnesota, and Iowa) embedded in both grasslands and croplands; our point estimates were nonsignificantly lower. An empirical study conducted in the neighboring state of Nebraska reported similar annual sediment accumulation rates ranging from 0.18 cm yr −1 to 0.29 cm yr −1 (Tang et al 2015). Wetlands embedded in agricultural fields had greater (non-overlapping 95 % CIs) annual sediment accumulation rates than wetlands surrounded by predominantly grassland in both Gleason's and our studies ( Table 2).…”
Section: Comparison With Empirical Studiessupporting
confidence: 71%
“…In this region, agricultural fields are often bare soil (no cover crop) in the non-growing seasons; these bare fields are subject to erosion for over half the year, and are the primary source of sediments that wind up in playa basins. In a field survey of 40 dry playas (i.e., basins with no water currently in them) in Texas, sediment depths at the soil surface ranged from 17 to 1049 mm (mean = 249 mm) and were deeper playas surrounded by tilled cropland [21]; similar sediment depths (means ranging from 230 to 380 mm) have been found in the Rainwater Basin playas of Nebraska [23]. The sediments that accumulate in playas have been found to be from waterborne rather than windborne particles, resulting from watershed erosion that is exacerbated in croplands that are irrigated relative to non-irrigated agricultural fields [24].…”
Section: Background and Rationalementioning
confidence: 63%
“…In recognition of the broad, overlapping fundamental and realized niches of cedar, the roles of fire and dispersal in shaping its range beyond the realized niche, and the well-documented influences of humans on fire and dispersal, we interpret current cedar spread in Great Plains landscapes as a process of "culturally induced range infilling," a modification of the term "culturally accelerated sediment accumulation" from wetland studies (Tang et al 2015). Following human removal of the restraining effect of fire from cedar populations, landscapes have crossed fire-free time thresholds and cedar has been freed to fill unoccupied portions of its realized niche, with the only remaining major constraint being dispersal time lags (Fig.…”
Section: Cultural Influences On Range Dynamicsmentioning
confidence: 99%